The association between sugar-sweetened beverages and hair loss in young women - Xiaojin Shi; Yucheng Yang; Haibing Yang; Juwei Zhang; Shuran Zhang; Xiaona Na; Dongying Fan; Yulin Zhang; Menglu Xi; Yuefeng Tan; Celi Yang; Junhan Zhang; et al. (Food Science and Human Wellness)
The association between sugar-sweetened beverages (SSBs) intake and hair loss condition might give scientific support for better dietary practices to prevent hair loss. We aimed to explore the association of SSBs intake with the hair loss condition in women. This online cross-sectional study, conducted from January 2022 to April 2022, recruited 1169 women aged 18−45 years from 31 provinces on mainland of China. We used the updated version of the 15-item Beverage Intake Questionnaire (BEVQ-15) to evaluate the usual beverage consumption over the past month and the Hair-Shedding Visual Scale for Asian Women (HSVS-A) to evaluate the extent of hair shedding. We utilized binary logistic regression to assess the association between SSBs intake and hair loss. Among 1169 female participants with an average age of 27.2, there were 211 (18.0%) participants with hair loss. Compared with participants who never drank SSBs, those who drank more than 7 times/week or 1000 mL/week were more likely to have hair loss, with an adjusted odds ratio (OR) of 2.25 (95% confidence interval (CI) = 1.32, 3.83) or 2.22 (95% CI = 1.28, 3.85). Furthermore, the mediation effect of anxiety status on the association between SSBs and female hair loss was observed, with a significant indirect effect (βindirect = 0.019 9, 95% CI = 0.003 2, 0.041 8). In conclusion, our study showed that women who consumed higher amounts of SSBs had an increased risk of hair loss, which might attract more attention from young women and benefit from reducing SSBs consumption. Further longitudinal and interventional studies are still needed to confirm the current association and provide evidenced-based health education.